A comparison of transporters’ paddle use when unloading pigs at slaughter - Bornhede, Maria (2014)
Today, pigs are moved on farm, between farms, between countries and to abattoirs. This movement of live pigs requires handling practices that are designed for the purpose. The objective of this study was to research the use of paddle in moving pigs, to investigate if there were different methods of paddle practice, explore the time efficiency of different kinds of paddle use and if there were any time variations in methods that varied in intensity of touch. This study was done on two Swedish abattoirs for a total of five weeks. A total of 22 transporters working at two different abattoirs where studied during unloading of pigs at the abattoirs. It was registered how the staff used the paddle, the size of each compartment in the truck and the time it took to move pigs out of each compartment. The total number of touches to the pigs, other use of paddle and the force with which these touches were directed was noted. There were differences among staff on time to move pigs and the methods used for moving. Staff differed in frequency of touches to animals, the proportion of paddle use that ended in physical contact with the pigs and the force of touches to pigs. There was a trend towards touches of less force to be more time efficient. The number of touches did increase with time of moving but the frequency did not generally increase with time, suggesting that an increased frequency of touch will not increase efficiency of moving pigs. Transporters were scored for paddle touch intensity and the time to move pigs was compared. There was a tendency towards less intense methods to be more time efficient than more intense methods of moving pigs.